Fatigue and associated factors in men with rheumatoid arthritis: a case-control study using the FACIT-F scale - Nolla, Joan M.; Valencia-Muntalà, Lidia; Berbel-Arcobé, Laura; Benavent, Diego; Vidal-Montal, Paola; Aguilar-Coll, Martí; Roig-Kim, Montserrat; Narváez, Javier; Gómez-Vaquero, Carmen (Frontiers in Medicine, 2025)
IntroductionFatigue is a debilitating condition commonly reported in rheumatoid arthritis (RA), yet its prevalence and associated factors in men remain underexplored. This study investigates the prevalence and severity of fatigue in Spanish men over 50 years with RA.MethodsA case-control study was conducted at a university hospital, comprising 84 RA patients (mean age: 71.9 ± 8.5 years) and 102 age-matched controls. Fatigue was assessed using the FACIT-F scale, together with evaluations of inflammatory markers (CRP, ESR), disease activity (DAS28, RAPID3), disability (HAQ), and health-related quality of life (SF-12). Group differences were examined, and correlations were analyzed to investigate associations between fatigue and RA-related parameters. Stepwise regression analysis was performed to identify independent predictors of fatigue.ResultsRheumatoid arthritis patients exhibited greater fatigue compared to controls, with a median FACIT-F score of 41.5 (38; 46.8) versus 46.25 (38; 49) (p < 0.05). Fatigue was prevalent among RA patients and showed negative correlations with inflammatory markers (ESR: r = −0.285, p < 0.01; CRP: r = −0.232, p < 0.01) and disease activity indices (DAS28: r = −0.330, p < 0.01; RAPID3: r = −0.475, p < 0.01). Positive correlations were observed with the SF-12 physical (r = 0.465, p < 0.01) and mental health components (r = 0.438, p < 0.01). RAPID3, SF-12, and ESR were the primary predictors of fatigue, collectively explaining up to 42.1% of its variance.ConclusionFatigue is a significant comorbidity in men with RA, closely linked to inflammation, disease activity and reduced quality of life.